Analisis Transparansi dan Akuntabilitas Pelayanan Publik dalam Implementasi SPMB Online pada Dinas Pendidikan dan Kebudayaan Kabupaten Biak Numfor - Maharini Sinatra; Hermanu Iriawan; Edyanto Edyanto (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The implementation of the Online Student Admission Selection System (SPMB Online) is a strategic public service innovation in the education sector aimed at improving efficiency, openness, fairness, and accountability in the student admission process. However, in an archipelago region like Biak Numfor Regency, this practice faces challenges such as infrastructure network limits, public digital literacy, and administrative readiness. This study aims to analyze the transparency and accountability of public services in the implementation of SPMB Online at the Department of Education and Culture of Biak Numfor Regency, as well as to identify supporting and inhibiting factors. Using a qualitative research method with a descriptive approach, data were collected through in-depth interviews, non-participatory observation, and documentation study. Informants were selected purposively, including department heads, system operators, school principals, and parents. Data analysis refers to the interactive model of Miles, Huberman, and Saldaña. The results indicate that the implementation of SPMB Online generally reflects the principles of transparency through the availability and accessibility of public information regarding regulations, criteria, schedules, and real-time ranking results. Accountability is met through alignment with the Technical Guidelines (Juknis) and structured monitoring and evaluation mechanisms. The main obstacles found include server instability during peak user traffic, uneven internet coverage, and low public digital literacy. This study recommends expanding server capacity, strengthening public socialization, and establishing integrated helpdesks at the district level to optimize equitable service delivery.